The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41598-018-38040-1
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA methylation of M1-macrophage genes in coronary artery disease

Abstract: M1 and M2 macrophage balance in atherosclerosis has attracted much interest. Though, it remains unknown how macrophage heterogeneity is regulated. Moreover, the regulation of macrophage polarization and activation also involve DNA methylation. However, it remains ambiguous which genes are under direct regulation by DNA methylation. Our aim was to evaluate the gene-specific promoter DNA methylation status of M1/M2 polarization markers in PBMCs of CAD patients. A case-control study was performed with 25 CAD pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 62 publications
3
14
0
1
Order By: Relevance
“…Previous studies have shown that abnormal DNA methylation in gene promoter regions is commonly related to AS [1620]. Bakshi et al showed that the methylation levels of STAT1, IL12b, MHC2, iNOS, JAK1, and JAK2 were higher in coronary artery disease (CAD) patients than in control subjects [21]. Another study showed increased levels of the DNA demethylase TET1 and decreased levels of DNMT1 in atherosclerotic plaques [22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that abnormal DNA methylation in gene promoter regions is commonly related to AS [1620]. Bakshi et al showed that the methylation levels of STAT1, IL12b, MHC2, iNOS, JAK1, and JAK2 were higher in coronary artery disease (CAD) patients than in control subjects [21]. Another study showed increased levels of the DNA demethylase TET1 and decreased levels of DNMT1 in atherosclerotic plaques [22].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in DNA methylation have been associated with the biological and pathophysiological mechanisms of CVD (100)(101)(102)(103)(104)(105)(106)(107)(108)(109). Frequently, studies show an association of DNA methylation of repetitive sequences such as LINE1 (>500,000 copies, accounting for about 20% of the genome (109) with various types of CVD (100,(102)(103)(104)110).…”
Section: Epigenomicsmentioning
confidence: 99%
“…With advances in technologies for DNA methylation profiling, molecular epidemiologic studies show an association of genomewide DNA methylation alterations with CVD (103,(105)(106)(107)(108). A meta-analysis from 11,461 individuals identified seven differentially-methylated CpGs, annotated to DTX3L-PARP3, NLRC5, and ABO (105).…”
Section: Epigenomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence mentioned above reveals that aberrant DNA methylation modification exists in aging-related vascular diseases and might be a potential biomarker for the diagnosis and prognosis of vascular aging-related diseases ( Liu and Tang, 2019 ). Gene at DNA methylation status based on monocyte/macrophage might work as a diagnostic biomarker for clinical application ( Bakshi et al, 2019 ). Notably, hyperhomocysteine is associated with CVD, potentially influencing DNA methylation modification, suggesting that DNA methylation is a biomarker for the increased risk of CVD ( Kim et al, 2010 ).…”
Section: Dna Methylation As a Diagnostic Tool And Therapeutic Target In Vascular Aging-related Diseasesmentioning
confidence: 99%